“Birdless Sky”. On one of the topoi in Lager literature (and its fringes) - Krupiński, Piotr (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2018)
The aim of the article is to indicate a recurring motif in the writings devoted to Nazi concentration camps. In many of the accounts of male and female internees the camp was described as a place “where birds did not sing”. As a territory over which there spun an empty silent sky. “A Birdless Sky”. The author of the study, utilising various sources, attempted to study the phenomenon from different perspectives. The results of scientific ornithological studies conducted by Günther Niethammer, a scientist and an SS guard at KL Auschwitz proved a rather unexpected point of reference for the voices of the internees. The presented article refers to the increasingly lively contemporary research into the topics of Lager and Holocaust literatures. Ecocriticism and environmentalism have been some of the more significant inspirations of the proposed discussion. By introducing a post-anthropocentric perspective, the author was able to expand the historical field to include non-human beings (animals, plants, landscapes).